Supplementary approaches to perinatal depression: a review of pathogenesis, herbal interventions, and dietary supplements - Yang, Quancheng; Lv, Yi; Gao, Shenrong; Zhang, Yu; Zhai, Xuejia (Frontiers in Psychology, 2025)
Although perinatal depression (PND) has garnered increasing attention, few specific pharmacological treatments exist, particularly for breastfeeding mothers concerned about antidepressant safety. The misconception that “natural is harmless” merits caution; herbal remedies and dietary supplements should be regarded as supplementary interventions pending robust safety evidence. This review summarizes recent advances in PND pathogenesis (neurotransmitter dysregulation, inflammation, hormonal imbalance, and microbiota alterations) and emerging drug development strategies, alongside clinical evidence for herbal and dietary supplements. Randomized controlled trial (RCT) findings reveal that while interventions like saffron and vitamin D show promise, significant limitations persist, including inconsistent efficacy, limited long-term safety data, and potential interactions with perinatal physiology. Caution is warranted until comprehensive studies validate the safety and reliability of natural interventions. This review underscores the need for rigorous trials to identify safe, effective PND treatments, particularly for vulnerable populations.